Mapeamento do conhecimento explícito na avaliação in loco / SINAES: o uso da TI na representação gráfica de categorias - Rodrigues, Marconi Araújo (2014)
The discussion concerning the identification of the most important resources used by organizations, although not too significant, has been taking place in researches during the latest years. The continuous major focus consists in getting to know whether the financial and technological resources have a greater representation than the knowledge ones. Currently, there is no doubt related to the consensus which states knowledge as a significant, competitive and differential tool. From this perspective, much has been done to create mechanisms to identify, store and disseminate knowledge into the organizations, by using the contribution of the information technology (IT) backgrounds. On the other hand, there is a growing discussion about the assessments, particularly in regard to higher education, issuance nuclear part of several evaluative proposals adopted in the past. Today, the country has the National System of Higher Education Assessment (SINAES) as a new model of current assessment. Divided into three stages, this system is formed by: Learning Institute Evaluation (IES), Specific Evaluation (in loco) and National exam of student performance (ENADE). Thus, the main purpose of this research consists of representing graphically the mapping of knowledge about the categories of Evaluation in loco, based on laws, rules and procedures established by the National Assessment System of Higher Education, in business courses, demonstrating the usage of a technology information tool that is able to help in that knowledge explanation. It means, as a whole, to bring to the field of higher education assessment the discussion led by the knowledge management and the contributions that the latter can refer to the first. In methodological terms, this research uses a qualitative, applicative and descriptive approach, coming out from literature and documentary researches, taking account primary and secondary data. Concluding, it is notorious that both parts - theoretical and practical - are surely justified because of the importance in knowledge management, mostly for the professionals who depend on outsourcing of this specific knowledge because of the systematic evaluations procedures. It was also required a reflection regarding the whole usage of TI on the social knowledge management context, as well as a graphical representation of reference applied in the assessment in loco (SINAES) with any IES, taking account the specifications of each course